(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
This article reports a study that investigated the effect of supervision of Functional Analytic Psychotherapy (FAP) on the therapist’s identification of client’s clinically relevant behaviors (CRB). The method consisted of an A/B design applied to 15 psychotherapy sessions. The sessions were conducted by a trainee therapist and his client whose clinical problems centered on interpersonal difficulties. During the five sessions, the therapist received traditional supervision and read additional material relevant to assertive behaviors. Since the 5th session the therapist received supervision in conducting FAP. The main supervision components were: 1) complete an idiographic questionnaire (FIAT) comprising five interpersonal behavior patterns; 2) the direct shaping of therapist behaviors, conducted by supervisor during the supervision session, focusing the relevant interpersonal behaviors for the therapy; 3) directing readings about FAP and a discussion of those readings; 4) and clarifications about the client’s CRB. The results indicated that after the FAP introduction, the therapist tended to recognize and report more client behaviors related to clinical change and also made more verbalizations related to self-knowledge; while the indications of behaviors related to the clinical problem tended to decrease through sessions. The results indicated that the therapist tended to perceive new dimensions of the client’s behavior. Such data were discussed in terms of the FAP contribution for promoting clinical change; that is, clinical change is more likely if those dimensions can be noticed and used by the therapist in directly shaping in-session client behaviors.